Analisis Hukum Tindak Pidana Pencurian dengan Kekerasan: Studi Kasus Putusan MA No. 448K/PID/2016 - Sitanggang, Valentina; Sibarani, Ruth Astrid; Butarbutar, Marolop (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2024)
This research discusses the analysis of criminal acts of theft with violence, with a case study of Decision No. 448 K/PID/2016 Pekanbaru District Court. This research refers to the increase in crime cases in Indonesia, especially theft, which can harm individuals and society. This research focuses on cases of criminal acts of violent theft involving the defendant Febriadi Panjaitan Alias Adi and hiscolleagues. This research uses normative juridical methods with specifications for using primary and secondary data as well as the application of the law by judges. Criminal sanctions against perpetrators of violent theft are heavier than ordinary theft. Research findings show that the defendant and his colleagues were proven guilty of committing violent theft which resulted in the death of the victim. The Pekanbaru District Court's decision initially imposed a prison sentence of 7 years, then the Pekanbaru High Court upheld the decision by increasing thesentence to 8 years, and the Supreme Court rejected the appeal.